In vitro virucidal activity of sodium hypochlorite against canine parvovirus type 2. Issue 15 (4th September 2018) - Cavalli, A.; Marinaro, M.; Desario, C.; Corrente, M.; Camero, M.; Buonavoglia, C.
Abstract: Canine parvovirosis is a very contagious, severe and often lethal infectious disease of dogs caused by canine parvovirus type 2 (CPV-2). Parvoviruses are very resistant to several disinfectants while are sensitive to halogens such as sodium hypochlorite which is often used for decontamination of veterinary clinics and animal housing facilities due to its broad spectrum of activity. If compliance with vaccination programmes and with proper disinfection plans is ensured, there should be no continuous, nor frequent, CPV-2 outbreaks in kennels and veterinary clinics. However, a continuous spread of CPV-2 infections is observed, even in kennels where an appropriate vaccination programme is applied, and this imposes a re-evaluation of disinfection protocols using sodium hypochlorite. The aim of the present study was to determine the effect of concentration, contact time and presence of organic matter on the virucidal activity of sodium hypochlorite against several CPV-2 strains. A sensitive in vitro assay capable of measuring the infectivity of CPV-2 was employed to determine the efficacy of three different concentrations of sodium hypochlorite. The data indicate that using a 0.75% sodium hypochlorite solution for a short contact time (1 min) can reduce significantly the CPV-2 titres and that even lower concentrations, i.e. 0.37%, can efficiently inactivate the viruses provided that the contact time is extended to 15 min. Results also confirm the importance of cleaning before disinfection since the presence of organic matter totally abrogated the virucidal activity of sodium hypochlorite solutions against the three CPV-2 strains.